Religiosity, Psychosocial Factors, and Well-Being: An Examination Among a National Sample of Chileans - Bilbao-Ramirez, M; Martinez-Zelaya, G (American Psychological Association Inc., 2018)
In this study, we analyzed the association between public religiosity, private religiosity, and life satisfaction in a representative sample of the Chilean population. Religiosity was associated with low income and low socioeconomic status and with being older and female. These variables were negatively associated with satisfaction with life. However, attendance at collective religious rituals was associated with life satisfaction, while private religiosity was unrelated. These results support the view that it is the social aspect of religion that benefits well-being. Controlling for gender, age, and socioeconomic variables, public religiosity predicts life satisfaction. Participation in religious rituals was associated with high social support and affect balance (low negative and high positive affect). Mediational analyses that included all variables related to public religiosity (main predictor) and to life satisfaction (dependent variable) showed that attendance to religious rituals had a direct effect on well-being, and also a significant indirect effect on well-being through high social support and low negative affect. Results are discussed with respect to the role of public rituals in the Chilean collectivistic culture. © 2018 American Psychological Association.
Keywords: religiosity; well-being; public rituals; psychosocial factors